Forensic data and microvariant sequence characterization of 27 Y-STR loci analyzed in four Eastern African countries. (March 2017) - Iacovacci, Giuseppe; D'Atanasio, Eugenia; Marini, Ornella; Coppa, Alfredo; Sellitto, Daniele; Trombetta, Beniamino; Berti, Andrea; Cruciani, Fulvio
Graphical abstract: Highlights: Sequence information regarding microvariants at four Y-STR loci is reported. Diversity at the palindromic DYF387S1 STR is shaped by non-allelic gene conversion. An excess of diallelic patterns at RM Y-STRs from cell lines was observed. Low intra- and high inter-population diversity values are observed. Ten additional Y-STRs in Yfiler Plus vs. Yfiler resulted in a 15% DC increase. Abstract: By using the recently introduced 6-dye Yfiler ® Plus multiplex, we analyzed 462 males belonging to 20 ethnic groups from four eastern African countries (Eritrea, Ethiopia, Djibouti and Kenya). Through a Y-STR sequence analysis, combined with 62 SNP-based haplogroup information, we were able to classify observed microvariant alleles at four Y-STR loci as either monophyletic (DYF387S1 and DYS458) or recurrent (DYS449 and DYS627). We found evidence of non-allelic gene conversion among paralogous STRs of the two-copy locus DYF387S1. Twenty-two diallelic and triallelic patterns observed at 13 different loci were found to be significantly over-represented (p < 10 −6 ) among profiles obtained from cell lines compared to those from blood and saliva. Most of the diallelic/triallelic patterns from cell lines involved recurrent mutations at rapidly mutating loci (RM Y-STRs) included in the multiplex (p < 10 −2 ). At haplotype level, intra-population diversity indices were found to be among the lowest so far reported for the Yfiler ® Plus, while statistically significant differences among countries and ethnic groups were detected when considering haplotype frequencies alone (FST ) or by using molecular distances among haplotypes (ΦST ). The strong population subdivision observed is probably the consequence of the patrilineal social organization of most eastern African ethnic groups, and suggests caution in the use of country-based haplotype frequency distributions for forensic inferences in this region.